THE USING OF FIGURATIVE LANGUAGE IN THE SONG LYRICS BY MAHER ZAIN - Rafika Purba; Ersika Puspita Dani; Sulastri .; Rini Ria (Jurnal Education and Development, 2021)
Music and song is the part of this world of songs, an art based on the organization of sound in time. But many of them do not know about the meaning and messages of the song lyrics which they listen. In this thesis the writer would find out the figurative language of Islamic song by Maher Zain which has deep meaning and more messages for the listener, not only enjoy listening to music but also the listener and reader will gets knowledge about Islam more increase. The aims of the research are: To find out the types of figurative language are used in Maher Zain‟s songs, and to find out the most dominant figurative language in Maher Zain‟s songs. In this research, the writer used the qualitative research since the data are in the form of written or oral words the techniques of collecting data, the collected from the song lyrics. entitled “Insya Allah‟ by Maher Zain released in November 2009. And the writer did 8 steps to the techniques of analysis data, follows: listening the songs, reading the song lyrics, underlining the word which related in figurative language, identifying, classifies certain lyrics, reanalyzed the song lyrics, and coding.